Cenomanian ammonite faunas from the Woodbine Formation and lower part of the Eagle Ford Group, Texas - Kennedy, W; Cobban, W (1990)
The ammonite faunas of the Woodbine Formation and lower part of the Eagle Ford Group of north-east and central Texas can be referred to five successive zonal assemblages of the standard sequence recognized for the southern part of the US Western Interior. The upper lower Cenomanian Forbesiceras brundrettei zone is represented by a limited assemblage in old collections believed to be from the Pepper Shale Member of the Woodbine, and from the Waco area. The middle Cenomanian Conlinoceras tarrantense zone is represented in the Tarrant Formation of the Eagle Ford in the area west of Dallas. The succeeding Acanthoceras bellense zone is a new biostratigraphic unit in the area, occurring only at the base of the Bluebonnet Member of the Lake Waco Formation of the Eagle Ford Group near Belton in Bell County. The Acanthoceras amphibolum zone is represented by the type species in the Lewisville Member of the Woodbine. The Six Flags Limestone Member of the Woodbine and the lower part of the bentonitic member of the Eagle Ford Group yield the index species and Tarrantoceras west of Dallas. The highest fauna described is that of the Plesiacanthoceras wyomingense zone, known only from the Templeton Member of the Woodbine in the northeastern part of the study area. -from Authors